Networks, Labour and Migration among Indian Muslim Artisans - Chambers, Thomas (Economic Exposure in Asia, 2020)
Networks, Labour and Migration among Indian Muslim Artisans provides an ethnography of life, work and migration in a North Indian Muslim-dominated woodworking industry. It traces artisanal connections within the local context, during migration within India, and to the Gulf, examining how woodworkers utilise local and transnational networks, based on identity, religiosity, and affective circulations, to access resources, support and forms of mutuality. However, the book also illustrates how liberalisation, intensifying forms of marginalisation and incorporation into global production networks have led to spatial pressures, fragmentation of artisanal labour, and forms of enclavement that persist despite geographical mobility and connectedness. By working across the dialectic of marginality and connectedness, Thomas Chambers thinks through these complexities and dualities by providing an ethnographic account that shares everyday life with artisans and others in the industry. Descriptive detail is intersected with spatial scales of 'local', 'national' and 'international', with the demands of supply chains and labour markets within India and abroad, with structural conditions, and with forms of change and continuity. Empirically, then, the book provides a detailed account of a specific locale, but also contributes to broader theoretical debates centring on theorisations of margins, borders, connections, networks, embeddedness, neoliberalism, subjectivities, and economic or social flux.